The Legend of the First Woman in Dante Gabriel Rossetti’s “The House of Life” - Al-Janabi , Sajid (Dirasat: Human and Social Sciences, 2022)
Various accounts of the First Woman’s story were included in sacred scripts regarding a woman who preceded Eve in the creation and addressed the role of being Adam’s wife. Lilith, the first female creature who showcased physical and oral resistance to God’s command, had acquired great attention in theological manuscripts and literary reproductions throughout history. This paper explores the enigmatic emergence of Lilith and the subsequent manipulations of her character. Moreover, it traces the chronological evolvement of her tale from the Talmudic Rabbinic tradition to the Victorian era. Also, it tackles the author’s religious advocacy related to the examination of Lilith’s choices and inspections of different experiences. The significance of the study lies in the literary and cultural perceptions of her story as a ‘fable’ or ‘biblical tale’ since it was rendered differently with varying levels of acceptance concerning its origin and employment to cultural and social contexts. The controversial treatment of her personality served multiple purposes through the oral tradition and written texts in different cultures. Dante Gabriel Rossetti was one of the poets who found in Lilith an inevitable means of manifesting trembling thoughts in his world. She offered him a good chance for relieving these thoughts by pouring them into painting and poetry. In this respect, the paper also sheds light on the portrayal of Lilith in two poems from Rossetti’s The House of Life with emphasis on his unique way of representing her as a cultural icon that best reflects the prerequisites of femininity.